The Effect of Realistic Mathematics Education on the Mathematical Problem-Solving Ability of Fifth-Grade Students at SD 21 Banda Aceh - Hayati, Zikra; Razia, Indah; Yacob, Fakhri (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
This research to examine the effect of implementing the Realistic Mathematics Education (RME) model on students' mathematical problem-solving abilities. This research employs a quantitative approach with a quasi-experimental design, specifically a control group pretest–posttest design. The sampling technique used is random sampling. The population of this study consisted of fifth-grade students, while the sample consisted of two groups: an experimental group consisting of 17 students taught using the RME model, and a control group consisting of 17 students taught using conventional instruction. Data were collected using a mathematical problem-solving ability test. Data analysis was conducted using an independent sample t-test with the assistance of SPSS version 26 for Windows. The results indicate a significant difference between the group that received the RME treatment and the group that received conventional instruction, with a significance value of 0.003 < 0.05. This finding demonstrates that the implementation of the RME model has a significant effect on improving students' mathematical problem-solving abilities. Therefore, the RME model can serve as an effective alternative instructional approach to enhance problem-solving skills among elementary school students.